Literature Review: Orientation and Mobility Assistive Technology for Students with Visual Impairment - Nerri, Ida Alfa; Purbaningrum, Endang; Wijiastuti, Asri; Andajani, Sri Joeda; Siddik, Md Abu Bakor (Journal of ICSAR, 2023)
The development of increasingly sophisticated technology is accompanied by the discovery of new assistive devices that should be accessible to all people, including the blind in order to maintain or improve functions so as to improve welfare. This study uses a literature review method with descriptive analysis by analyzing 20 articles. The purpose of this research is to examine more related to assistive technology for the blind in navigating indoors and outdoors including buildings and the accessibility of public services. The literature search was carried out through an electronic search for publications from ERIC, Researchgate, Spingerlink, Sage, Science Direct, Google Scholar and IEEE Xplore. The results of the study describe the use of various assistive technologies for the visually impaired related to navigation in spaces or buildings and even the wider environment as well as public services that are commonly accessed by the public. Furthermore, it is related to the existence of a brief description of the assistive technology developed and the benefits of the results of the development for users.